2009
DOI: 10.7863/jum.2009.28.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Sonographic and Clinical Parameters in the Prediction of Retained Products of Conception

Abstract: Objective. The purpose of this study was to assess the diagnostic accuracy of different parameters (clinical and sonographic) in the prediction and management of retained products of conception (RPOC) in the late postpartum period. Methods. This was a prospective cohort 3-year audit. Predefined data were collected and compared with histopathologic (HP) reports after uterine evacuation. The primary outcome measure was the diagnostic accuracy of different clinical and sonographic parameters, including color Dopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 10 publications
5
28
0
Order By: Relevance
“…A presenting sign of vaginal bleeding was more prevalent in women with pathologically confirmed RPOC after spontaneous term vaginal delivery compared to those after pregnancy termination (table 2). These findings corroborate with a previously reported study, which explored the diagnostic accuracy of several clinical parameters in the prediction of RPOC and found that postpartum hemorrhage had the highest sensitivity, positive predictive value and positive likelihood ratio rates as compared with the other clinical symptoms [14]. …”
Section: Discussionsupporting
confidence: 81%
“…A presenting sign of vaginal bleeding was more prevalent in women with pathologically confirmed RPOC after spontaneous term vaginal delivery compared to those after pregnancy termination (table 2). These findings corroborate with a previously reported study, which explored the diagnostic accuracy of several clinical parameters in the prediction of RPOC and found that postpartum hemorrhage had the highest sensitivity, positive predictive value and positive likelihood ratio rates as compared with the other clinical symptoms [14]. …”
Section: Discussionsupporting
confidence: 81%
“…Using histopathology as confirmatory test, the overall sensitivity of TVS for diagnosis of RPOC in present study is 92% which is comparable to study conducted by De Vries et al, Matijevic et al and Esmaeillou et al [11][12][13] The overall specificity of TVS is 60%, which is comparable to that in study conducted by Esmaeillou et al, higher than in study conducted by Matijevic et but lower than other studies. 12,13 This is because of relatively high number of false positive results which might be due to false interpretation of blood clot for RPOC which also looks like echogenic mass on ultrasound or presence of thickened endometrium giving impression of RPOC but proved to be thickened decidua with absence of chorionic villi on histopathology.…”
Section: Discussionsupporting
confidence: 79%
“…12,13 This is because of relatively high number of false positive results which might be due to false interpretation of blood clot for RPOC which also looks like echogenic mass on ultrasound or presence of thickened endometrium giving impression of RPOC but proved to be thickened decidua with absence of chorionic villi on histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of US for the diagnosis of RPOC varies widely based on the diagnostic criteria and the clinical setting. However, more recent studies have defined more robust gray-scale and color Doppler US criteria with a high sensitivity and specificity for RPOC (7,8,(16)(17)(18)(19)(20)(21) (Table). …”
Section: Us Diagnosis Of Rpocmentioning
confidence: 98%